International banking conglomerates and the transmission of lending shocks across borders - Reint Gropp; Deyan Radev (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2017)
We investigate how solvency and wholesale funding shocks to 84 OECD parent banks affect the lending of 375 foreign subsidiaries. We find that parent solvency shocks are more important than wholesale funding shocks for subsidiary lending. Furthermore, we find that parent undercapitalization does not affect the transmission of shocks, while wholesale shocks transmit to foreign subsidiaries of parents that rely primarily on wholesale funding. We also find that transmission is affected by the strategic role of the subsidiary for the parent and follows a locational, rather than an organizational pecking order. Surprisingly, liquidity regulation exacerbates the transmission of adverse wholesale shocks. We further document that parent banks tend to use their own capital and liquidity buffers first, before transmitting. Finally, we show that solvency shocks have higher impact on large subsidiary banks with low growth opportunities in mature markets.
urn:nbn:de:hebis:30:3-437477
Keywords: G01; G21; G28; 330; commercial banks; global banks; wholesale shocks; solvency shocks; transmission; internal capital markets